Uses of epidemiology in housing programmes and in planning human settlements : report of a WHO expert committee on housing and health. - World health organization. Expert committee on housing and health (Geneva : World health organization, 1974)
Hoe kunnen we bij het plannen van menselijke bewoning rekening houden met mogelijke epidemies?